2018
DOI: 10.1002/term.2658
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of specific carbohydrates results in enhanced deposition of chondrogenic-specific matrix during mesenchymal stem cell differentiation

Abstract: Repair or regeneration of hyaline cartilage in knees, shoulders, intervertebral discs, and other assorted joints is a major therapeutic target. To date, therapeutic strategies utilizing chondrocytes or mesenchymal stem cells are limited by expandability or the generation of mechanically inferior cartilage. Our objective is to generate robust cartilage-specific matrix from human mesenchymal stem cells suitable for further therapeutic development. Human mesenchymal stem cells, in an alginate 3D format, were supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
(36 reference statements)
2
6
0
Order By: Relevance
“…Additionally, the sulfation patterns in the GAG chains play crucial roles by allowing interactions, mainly of an ionic nature, with growth factors, cell surface receptors, enzymes, cytokines, chemokines and proteins that are associated with several biological processes, such as development, disease, cell growth and differentiation and microbial pathogenesis [20][21][22][23]. In fact, GAGs role in controlling stem cell fate through modulation of important signaling pathways such as FGF signaling was previously suggested [18,21,24], Additionally, the effects of different GAGs in MSC proliferation and differentiation through mediation of growth factor activity have also been reported in the literature [25][26][27][28], Therefore, the structural and growth factor sequestering/activation properties of GAGs make these biomolecules promising materials for a broad range of tissue engineering applications [19,20,29], As major components of cartilage, GAGs, mainly CS and HA, have been incorporated in tissue engineering scaffolds to more effectively mimic the natural ECM and improve the quality of the generated tissue [30][31][32].…”
Section: Introductionmentioning
confidence: 92%
“…Additionally, the sulfation patterns in the GAG chains play crucial roles by allowing interactions, mainly of an ionic nature, with growth factors, cell surface receptors, enzymes, cytokines, chemokines and proteins that are associated with several biological processes, such as development, disease, cell growth and differentiation and microbial pathogenesis [20][21][22][23]. In fact, GAGs role in controlling stem cell fate through modulation of important signaling pathways such as FGF signaling was previously suggested [18,21,24], Additionally, the effects of different GAGs in MSC proliferation and differentiation through mediation of growth factor activity have also been reported in the literature [25][26][27][28], Therefore, the structural and growth factor sequestering/activation properties of GAGs make these biomolecules promising materials for a broad range of tissue engineering applications [19,20,29], As major components of cartilage, GAGs, mainly CS and HA, have been incorporated in tissue engineering scaffolds to more effectively mimic the natural ECM and improve the quality of the generated tissue [30][31][32].…”
Section: Introductionmentioning
confidence: 92%
“…Sodium alginate is the sodium salt of alginate; it remains in the sol condition in aqueous solution and can be gelated by the addition of CaCl 2 . This character has been applied for human mesenchymal stem cell proliferation and chondrogenic differentiation in a three-dimensional (3D) alginate scaffold [ 22 , 23 ]. In addition, fundamental research in this area has shown that alginate promotes IVD repair [ 16 , 17 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…For ATDC5, staining was slightly stronger on day 21 than on day 14, and the expression levels of aggrecan ( Figure 2A ) and type II collagen ( Figure 2B ) were upregulated with increasing galactose concentrations, demonstrating that galactose can successfully promote chondrogenesis. In addition, as investigated in other articles, the estimated half-life of proteoglycans is about 26 days, while that of collagen is over 100 years ( Lai et al, 2013 ; Linka et al, 2016 ; Christiansen-Weber et al, 2018 ). Both are longer than the experiment period in this work.…”
Section: Resultsmentioning
confidence: 74%
“…This molecule is also involved in a variety of pathways, regulating cellular phenotypes and metabolic pathways ( Radenkovic et al, 2019 ). Through this highly conserved Leloir pathway, galactose can be activated and act as a precursor for glycosylation or it can be converted to UDP-glucose, which then flows into glycogen synthesis or glycolysis, depending on the type of tissues and its energy requirements ( Petry and Reichardt, 1998 ; Holden et al, 2003 ; Coelho et al, 2015 ; Christiansen-Weber et al, 2018 ). In our study, the accumulation of aggrecan and type II collagen ( Figures 2 , 4 ) was successfully visualized by immunofluorescence staining, explicitly mapping the outcome of the Leloir pathway.…”
Section: Discussionmentioning
confidence: 99%